THE PHILOSOPHY AND DRIVING FORCES IN THE DEVELOPMENT OF MEASUREMENT SCIENCE - SOME VIEWS UPON THE PROBLEMS - Kalchev, Ivan (International Journal of Computing, 2002)
A necessary background for clear outlined existing of each science in the so fast changing world is its permanent development in theoretical and applied aspect for solving today’s problems and visions in the future. In this respect for the modern sciences, more important role play theories, that not only generalize and explain the known facts and phenomena, but serve for predicting and achieving new levels of knowledge. In this paper the methods of teaching in the discipline Distributed Measurement Systems and in particular, the laboratory exercises carrying out by the students of Faculty of Automation and English Language Department of Engineering in Technical University of Sofia are presented.